Integrated oxygen-doping and dye sensitization of graphitic carbon nitride for enhanced visible light photodegradation - Liu, S.; Sun, Hongqi; Ang, H.; Tade, Moses; Wang, Shaobin (Academic Press, 2016)
Graphitic carbon nitride (GCN) is a promising metal-free photocatalyst while suffering from low charge mobility induced inefficient photocatalysis. In this work, oxygen doping was employed to enhance the photodegradation of organic pollutants in water on graphitic carbon nitride (GCNO) under visible light. For further absorption extension, four organic dyes (Eosin-Y, Perylene, Nile-red and Coumarin) were adopted to dye-sensitize the GCNO photocatalyst. It was found that O-doping can promote dye sensitization, which was dependent on the type of dyes and influenced the photodegradation efficiencies of methylene blue (MB) and phenol. Nile-red sensitized GCNO presented the best activity in MB degradation under λ > 480 nm irradiations while Eosin-Y showed the best sensitization performance for phenol degradation under λ > 420 nm light source. However, dye sensitization was not effective for enhanced pollutant degradation on GCN without O-doping. UV–vis diffuse reflectance spectra (UV–vis DRS), photoluminescence (PL) spectra, and photocurrent analyses were applied to investigate the mechanism of carriers’ transfer, which indicated that dye molecules could inject extra electrons into GCNO energy band and the energy dislocation could suppress electron/hole recombination, enhancing photocatalytic performances.